Feasibility of creation and use of specialized search systems for scientific and technical information - M. F. Zianchuk; I. V. Saltanova (Системный анализ и прикладная информатика)
The efficiency of using global Internet search systems versus specialized systems, including the State System of Scientific and Technical Information of the Republic of Belarus, for searching the scientific and technical information is compared in this article. Potential advantages and disadvantages of STI search systems are considered. The experience of individual states in creating and maintaining the functioning of state resources of scientific and technical information is analyzed.